Mental health in elite sports. A continuum of strategies that athletic trainers can use to support competitive athletes with psychological issues: a scoping review - Jean-Bindley, Geneviève; Sauriol-Gauthier, Ana; Corbin-Berrigan, Laurie-Ann; Girard, Stéphanie (Frontiers in Psychology, 2025)
IntroductionAthletes are at high risk of experiencing psychological distress. It is unclear if professionals in charge of competitive athletes’ physical and psychological wellbeing are adequately trained to identify and manage psychological distress, despite many athletic trainers (ATs) reporting having held a position where it was necessary to counsel student-athletes on personal issues. However, ATs have also reported having received insufficient training to support athletes in the face of psychological distress.ObjectiveThe present scoping review aims to identify, in scientific literature, how ATs can improve the psychological support provided to competitive athletes.MethodsThis scoping review was carried out using a six-step process in accordance with the PRISMA-ScR guideline. The initial search, based on specific keywords related to ATs, athletes, strategies and mental health, identified a total of 1,204 articles. The research was conducted across 8 databases (APA PsycINFO, SPORTDiscuss, Google Scholar, Social Science Research Network-SSRN and others). The initial search, based on specific keywords related to ATs, athletes, strategies and mental health, identified a total of 1,204 articles. After removing duplicates, abstracts and titles were screened in accordance with the inclusion and exclusion criteria. Included articles were published between 2010 and 2024, written in English, on athletes aged 8–25 years, from Western cultures, participating in sport within a sport organization and presenting strategies that could assist ATs in the management of athletes with mental difficulties. The search yielded 22 articles that were relevant to the study.ResultsResults of retained articles were separated into four themes: (1) training; (2) prevention; (3) intervention strategies; and (4) referral. Prevention involves implementing a set of measures aimed at avoiding or reducing the number and severity of psychological distress. Training helps fill gaps in the understanding and application of psychological interventions in sport. Intervention strategies allow professionals to intervene based on meeting the fundamental psychological needs of athletes. Finally, as soon as signs of psychological distress are identified, it is important to refer the athlete to a mental health professional in order to provide adequate support to athletes.Discussion and conclusionBased on the results, two themes are most often reported, such as prevention and intervention strategies. Future research should explore the long-term impacts of these interventions implemented by ATs on athletes’ mental wellbeing.